2021
DOI: 10.1016/j.scitotenv.2020.143355
|View full text |Cite
|
Sign up to set email alerts
|

Associations between mortality from COVID-19 in two Italian regions and outdoor air pollution as assessed through tropospheric nitrogen dioxide

Abstract: After the appearance of COVID-19 in China last December 2019, Italy was the first European country to be severely affected by the outbreak. The first diagnosis in Italy was on February 20, 2020, followed by the establishment of a light and a tight lockdown on February 23 and on March 8, 2020, respectively. The virus spread rapidly, particularly in the North of the country in the ‘Padan Plain’ area, known as one of the most polluted regions in Europe. Air pollution has been recently hypothesized to enhance the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 58 publications
4
46
0
Order By: Relevance
“…However, access to population activity data is difficult. The environmental factors chosen for the study were mainly those reflecting population activities, but other natural conditions (e.g., air pollution, temperature, humidity) play an essential role in the transmission of the virus (e.g., Filippini et al, 2020 ; Guo et al, 2020 ; Zhang et al, 2020 ). Therefore, in future studies, these data need to be incorporated into the models.…”
Section: Discussionmentioning
confidence: 99%
“…However, access to population activity data is difficult. The environmental factors chosen for the study were mainly those reflecting population activities, but other natural conditions (e.g., air pollution, temperature, humidity) play an essential role in the transmission of the virus (e.g., Filippini et al, 2020 ; Guo et al, 2020 ; Zhang et al, 2020 ). Therefore, in future studies, these data need to be incorporated into the models.…”
Section: Discussionmentioning
confidence: 99%
“…There were no important local differences in attempted control until November 6, 2020, when area-specific policies driven by the local spread of the outbreak began ( DPCM, 2020 ). This history allows a relatively unconfounded comparison of the first and second waves of Covid-19 epidemiology during the February-October period between Italian communities, assuming that environmental and behavioral risk factors for Covid-19 such as outdoor air pollution, meteorological effects, and social interaction are close to uniform across Italy ( Ambika et al, 2021 ; Calina et al, 2021 ; Copat et al, 2020 ; Domingo and Rovira, 2020 ; Filippini et al, 2021 ; Filippini et al, 2020 ; Marques et al, 2021 ; Mele et al, 2021 ; Sidiropoulou et al, 2021 ; Sunyer et al, 2021 ; Tsatsakis et al, 2020b ). The vaccination campaign did not begin in Italy until December 27, 2020 ( Ministry of Health, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regions where most of the new cases and deaths are reported are still those of Northern Italy, and particularly Lombardy [ 7 ]. A large part of Northern Italy territory includes the Po basin area (Padan Plain), which is the most industrialized area of the country, and one of the most polluted region of Europe [ 8 ]. The World Health Organization (WHO), reported that air pollution is responsible for 7 million deaths worldwide every year, and represented one of the main concern regarding public health [ 9 ].…”
Section: Introductionmentioning
confidence: 99%